2015
DOI: 10.1155/2015/364020
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation Induces an Inflammatory Response in Preinjured Lungs in Late Phase of Sepsis

Abstract: Mechanical ventilation (MV) may amplify the lung-specific inflammatory response in preinjured lungs by elevating cytokine release and augmenting damage to the alveolar integrity. In this study, we test the hypothesis that MV exerts different negative impacts on inflammatory response at different time points of postlung injury. Basic lung injury was induced by cecal ligation and puncture (CLP) surgery in rats. Physiological indexes including blood gases were monitored during MV and samples were assessed followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(42 reference statements)
0
4
0
2
Order By: Relevance
“…The only association that we have found in this regard is that the majority of patients with very high levels of CCL2 (but not all) needed to receive invasive mechanical ventilation in the Intensive Care Unit. This observation could be explained by the combined effect of the greater severity of these patients together with an inflammatory reaction merely produced by the invasive intervention [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only association that we have found in this regard is that the majority of patients with very high levels of CCL2 (but not all) needed to receive invasive mechanical ventilation in the Intensive Care Unit. This observation could be explained by the combined effect of the greater severity of these patients together with an inflammatory reaction merely produced by the invasive intervention [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only association that we have found in this regard is that the majority of patients with very high levels of CCL2 (but not all) needed to receive invasive mechanical ventilation in the Intensive Care Unit. This observation could be explained by the combined effect of the greater severity of these patients together with an inflammatory reaction merely produced by the invasive intervention [46].…”
Section: Discussionmentioning
confidence: 98%
“…We found that in patients with acute cholangitis, sepsis is positively associated with age, ventilator-support time, diabetes, coagulopathy and an SBP less than 90 mmHg or greater than 140 mmHg; these findings are consistent with previous research. [21][22][23] Clinical treatments should focus on patients with these characteristics, and early treatment with antibiotics should be used to prevent the occurrence of sepsis.…”
Section: Discussionmentioning
confidence: 99%